Advanced strategic research to promote the use of rice genetic resources - Lee, Jae-Sung; Chebotarov, Dmytro; Platten, John Damien; McNally, Kenneth; Kohli, Ajay (MDPI, 2020)
International genebanks have a collection of over 760 K conserved accessions of various plants, most of these accessions are within the multi-lateral system governed by the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA). However, in spite of the success in collection and conservation, only a small portion of the genetic diversity has been used in crop breeding programs. As climate change-induced new or enhanced constraints seriously hamper crop productions, researchers and breeders should be able to swiftly choose an appropriate set of genetic resources from the genebank and use them for improving crop varieties. Here, we present some advanced technologies that can effectively promote the use of diverse rice accessions held at national/international genebanks. High throughput phenotyping using multispectral imaging systems and unmanned aerial vehicles (UAV) can quickly screen large numbers of accessions for various useful traits. Such data, when combined with that from the digital rice genebank consisting of genome sequencing data, will significantly increase the efficiency in breeding efforts. Recent genome sequencing data of the rice wild species will also add to the resources available for pre-breeding efforts such as the introgression of useful genes into modern rice varieties. We expect that these advanced technologies and strategies developed through the global rice research programs will be applicable for many closely related species as well.